1997
DOI: 10.1021/ed074p1218
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic versus Thermodynamic Control in the Dehydration of 2-Methylcyclopentanol: A Two-Part Laboratory Experiment Utilizing the Gignard Reaction and GC-MS

Abstract: was obtained from Eastman Kodak. Calcium chloride was obtained from J. T. Baker Chemical Co. (1313).GC-MS analyses were performed on a Hewlett Packard 5890 gas chromatograph coupled to a 5970 series mass selective detector. The column used was a Supelco 2-4026 15-m × 0.25-mm capillary column packed with SPBM-1 (0.25 µm). GC conditions were as follows: injector and detector temp = 200 °C; oven conditions: initial temp = 70 °C; initial time = 1 min, rate = 15°/min, final temp = 200 °C, final time = 1 min. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to the literature, kinetic alkenes isomerize to thermodynamic alkenes in acidic conditions. 38 These experimental observations indicate that the kinetic alkene 7x isomerized to the thermodynamic alkene 6x. The steric hindrance around H-1 was greater than that around H-2 on phosphite 4x, so that triethylamine primarily captured H-2 on the cyclopentyl ring moiety on 4x via pathway b with a regioselective E2-elimination reaction (Scheme 2).…”
Section: ) We Examined Endo-(1s)-(-)-177-trimethylbicyclo[221]mentioning
confidence: 88%
“…According to the literature, kinetic alkenes isomerize to thermodynamic alkenes in acidic conditions. 38 These experimental observations indicate that the kinetic alkene 7x isomerized to the thermodynamic alkene 6x. The steric hindrance around H-1 was greater than that around H-2 on phosphite 4x, so that triethylamine primarily captured H-2 on the cyclopentyl ring moiety on 4x via pathway b with a regioselective E2-elimination reaction (Scheme 2).…”
Section: ) We Examined Endo-(1s)-(-)-177-trimethylbicyclo[221]mentioning
confidence: 88%
“…The standardized ACS Organic Chemistry Exam, version 1998, 2 was administered in the final week of classes during the second semester to provide a basis for comparison of student performance before and after the implementation of the two-cycle strategy. Organic chemistry students in the first two years of this study (identified as 2001 and 2002 in Figure 2) completed a traditional, linear progression through the textbook and experienced a laboratory program based on solving puzzles (26)(27)(28)(29). Students in the last two years of organic chemistry (2003 and 2004) made two passes through the textbook and carried out student-designed research projects in the lab.…”
Section: Assessmentmentioning
confidence: 99%